Anda di halaman 1dari 25

# Beam deflection formulae www.vaxasoftware.

com

## Symbol Physical quantity Units

E·I Flexural rigidity N·m2, Pa·m4
y Deflection or deformation m
θ Slope, Slope of the deflection, Angle of rotation -
x Distance from support (origin) m
L Length of beam (without overhang) m
M Moment, Bending moment, Couple moment applied N·m
R Reaction load, reaction force N
V Shear force, shear N

## Simple beam - Uniformly distributed load

− w0 x 3
Deflection yAB = ( L − 2 Lx 2 + x 3 )
24 EI
− 5w0 L4 L
yMAX = at x =
384 EI 2
− w0 3
Slope θ AB = ( L − 6 Lx 2 + 4 x 3 )
24 EI
− w0 L3
θ A = −θ B =
24 EI
wx
Moment M AB = 0 ( L − x)
2
w0 L2 L
M MAX = at x =
8 2
w
Shear VAB = 0 ( L − 2 x)
2
wL
Reactions RA = RB = 0
2
Simple beam - Uniform load partially distributed at left end (I)
− w0 x
Deflection yAC = (9 L3 − 24 Lx 2 + 16 x 3 )
384 EI
− w0 L
yCB = (8 x 3 − 24 Lx 2 + 17 L2 x − L3 )
384 EI
− w0
Slope θ AC = (9 L3 − 72 Lx 2 + 64 x 3 )
384 EI
− w0 L
θ CB = (24 x 2 − 48Lx + 17 L2 )
384 EI
− 3wL3 7 wL3
θA = θB =
128EI 384 EI
w w
Moment M AC = 0 (3Lx − 4 x 2 ) M CB = 0 ( L2 − Lx)
8 8
w0 − w0 L
Shear VAC = (3L − 8 x) VCB =
8 8
VA = RA VB = − RB
3w L wL
Reactions RA = 0 RB = 0
8 8

## Simple beam - Uniform load partially distributed at left end (II)

Deflection:
− w0 x 4
yAC = (a − 4a 3 L + 4a 2 L2 + 2a 2 x 2 − 4aLx 2 + Lx 3 )
24 LEI
− w0 a 2
yCB = (−a 2 L + 4 L2 x + a 2 x − 6 Lx 2 + 2 x3 )
24 LEI
Slope:
− w0
θ AC = (a 4 − 4a 3 L + 4a 2 L2 + 6a 2 x 2 − 12aLx 2 + 4 Lx 3 )
24 LEI
− w0 a 2
θ CB = (4 L2 + a 2 − 12 Lx + 6 x 2 )
24 LEI
Moment:
− w0 2 w a2
M AC = (a x − 2aLx + Lx 2 ) M CB = 0 ( L − x)
2L 2L
Shear:
− w0 2 − w0 a 2
VAC = (a − 2aL + 2 Lx) VCB = VC = VB =
2L 2L
2
wa wa
Reactions RA = 0 (2 L − a) RB = 0
2L 2L
Simple beam - Uniform load partially distributed

RA x 3 R x3 w
Deflection yAC = + αx yCD = A − 0 ( x − a) 4 + αx
6 EI 6 EI 24 EI
R ( L − x) 3
β ( L − x)
yDB = B +
6 EI L
2
R x R x2 w
Slope: θ AC = A + α θ CD = A − 0 ( x − a)3 + α
2 EI 2 EI 6 EI
− RB ( L − x) 2
β
θ DB = −
2 EI L
w
Moment M AC = RA x M CD = RA x − 0 ( x − a) 2
2
M DB = RB ( L − x)
Shear VAC = VA = VC = RA VCD = RA − w0 ( x − a)
VDB = VD = VB = − RB
wb wb
Reactions RA = 0 (2c + b) RB = 0 (2a + b)
2L 2L
Where:
w b3 L − 6 EIβ − 3RBc 2 L − 3RA L(a + b) 2
α= 0
6 LEI
4w ab + 3w0b − 8RA (a + b)3 − 12 RBc 2 L + 8RBc 3
3 4
β= 0
24 EI

## Simple beam - Uniform load partially distributed at each end

w1 x 2
Moment M AC = RA x −
2
w1a w2 ( L − x) 2
M CD = RA x − (2 x − a) M DB = RB ( L − x) −
2 2
Shear:
VAC = RA − w1 x VCD = RA − w1a VDB = − RB + w2 ( L − x)
Reactions:
w a(2 L − a) + w2c 2 w c(2 L − c) + w1a 2
RA = 1 RB = 2
2L 2L
Simple beam - Load increasing uniformly to right end
− w0 x
Deflection y AB = (7 L4 − 10 L2 x 2 + 3x 4 )
360 LEI
w0 L4
yMAX = −0,00652 at x = 0,5193L
EI
− w0
Slope θ AB = (7 L4 − 30 L2 x 2 + 15 x 4 )
360 LEI
− 7 w0 L3 w0 L3
θA = θB =
360 EI 45 EI
w0 2
Moment M AB = (L x − x3 )
6L
w0 2
Shear VAB = ( L − 3x 2 )
6L
wL 2w L
Reactions RA = 0 RB = 0
6 6

## Simple beam - Load increasing uniformly to center

− w0 x
Deflection yAC = (5 L2 − 4 x 2 ) 2
960 LEI
− w0 ( L − x)
yCB = (5L2 − 4( L − x) 2 ) 2
960 LEI
− w0 L4 L
yMAX = at x =
120 EI 2
− w0
Slope θ AC = (5L2 − 4 x 2 )( L2 − 4 x 2 )
192 LEI
w0
θ CB = (5 L2 − 4( L − x) 2 )( L2 − 4( L − x) 2 )
192 LEI
− 5w0 L3
θ A = −θ B =
192 EI
w0
Moment M AC = (3L2 x − 4 x 3 )
12 L
w0 ( L − x)
M CB = (3L2 − 4( L − x) 2 )
12 L
w − w0 2
Shear VAC = 0 ( L2 − 4 x 2 ) VCB = ( L − 4( L − x) 2 )
4L 4L

w0 L
Reactions RA = RB =
4
Simple beam - Sinusoidal distributed load

− w0 L4 πx
Deflection yAB =4
sin
π EI L
−w L 4
L
yMAX = 4 0 at x =
π EI 2
−w L 3
πx − w L3
Slope θ AB = 3 0 cos θ A = −θ B = 3 0
π EI L π EI
2
wL πx
Moment M AB = 0 2 sin
π L
w0 L πx wL
Shear VAB = cos VA = −VB = 0
π L π
w0 L
Reactions RA = RB =
π

## Simple beam - Concentrated load at center

− Px
Deflection yAC = (3L2 − 4 x 2 )
48EI
− P( L − x)
yCB = (3L2 − 4( L − x) 2 )
48EI
− PL3 L
y MAX = yC = at x =
48EI 2
Slope:
−P 2 −P
θ AC = ( L − 4 x 2 ) θ CB = (4 x 2 − 8Lx + 3L2 )
16 EI 16 EI
2
PL
θ A = −θ B =
16 EI
Px P( L − x)
Moment M AC = M CB =
2 2
P −P
Shear VAC = VA = VCB = VB =
2 2
P
Reactions RA = RB =
2
Simple beam - Concentrated load at any point
− Pbx 2
Deflection yAC = (L − b2 − x 2 )
6 LEI
yCB =
− Pa( L − x) 2
6 LEI
[
L − a 2 − ( L − x) 2 ]
Slope:
θ AC =
− Pb 2
6 LEI
( L − b 2 − 3x 2 ) θ CB =
Pa 2
6 LEI
[L − a 2 − 3( L − x) 2 ]
− Pb( L − b )
2 2
Pa
θA = θB = ( L2 − a 2 )
6 LEI 6 LEI
Pbx Pa( L − x)
Moment M AC = M CB =
L L
Pb − Pa
Shear VAC = VA = VCB = VB =
L L
Pb Pa
Reactions RA = RB =
L L

## Simple beam - Two equal concentrated loads symmetrically placed

− Px
Deflection y AC = (3aL − 3a 2 − x 2 )
6 EI
− Pa
yCD = (3Lx − 3x 2 − a 2 )
6 EI
yDB =
− P( L − x)
6 EI
[
3aL − 3a 2 − ( L − x) 2 ]
− Pa L
y MAX = (3L2 − 4a 2 ) at x =
24 EI 2
−P − Pa
Slope θ AC = (aL − a 2 − x 2 ) θ CD = ( L − 2 x)
2 EI 2 EI
θ DB =
P
2 EI
[
aL − a 2 − ( L − x) 2]
− P(aL − a 2 )
θ A = −θ B =
2 EI
Moment M AC = Px M CD = Pa M DB = P( L − x)
Shear VAC = P VCD = 0 VDB = − P
Reactions RA = RB = P

## Simple beam - Two equal concentrated loads unsymmetrically placed

Moment M AC = RA x M CD = RA x − P( x − a)
M DB = RB ( L − x)
Shear VAC = RA VCD = RA − P VDB = − RB
P ( L − a + b) P( L − b + a)
Reactions RA = RB =
L L
Simple beam - Two unequal concentrated loads unsymmetrically placed
Moment M AC = RA x M CD = RA x − P1 ( x − a)
M DB = RB ( L − x)
Shear VAC = RA VCD = RA − P1 VDB = − RB
P ( L − a) + P2b P ( L − b) + P1a
Reactions RA = 1 RB = 2
L L

## Simple beam - Couple moment Mo at right end

− M0x 2
Deflection yAB = (L − x 2 )
6 LEI
− M0 2
Slope θ AB = ( L − 3x 2 )
6 LEI
− M0L M L
θA = θB = 0
6 EI 3EI
M0x
Moment M AB =
L
M
Shear VAB = 0
L
M − M0
Reactions RA = 0 RB =
L L

## Simple beam - Couple moment Mo at left end (I)

M0x
Deflection y AB = (2 L2 − 3Lx + x 2 )
6 LEI
M L2 ⎛3− 3 ⎞
y MAX = 0 at x = ⎜⎜ ⎟L

9 3EI ⎝ 3 ⎠
M0
Slope θ AB = (2 L2 − 6 Lx + 3x 2 )
6 LEI
M0L − M 0L
θA = θB =
3EI 6 EI
− M0
Moment M AB = ( L − x)
L
M
Shear VAB = 0
L
M0 − M0
Reactions RA = RB =
L L
Simple beam - Couple moment Mo at left end (II)
− M0x
Deflection yAB = (2 L2 − 3Lx + x 2 )
6 LEI
− M 0 L2 ⎛3− 3 ⎞
y MAX = at x = ⎜⎜ ⎟L

9 3EI ⎝ 3 ⎠
− M0
Slope θ AB = (2 L2 − 6 Lx + 3x 2 )
6 LEI
− M0L M L
θA = θB = 0
3EI 6 EI
M
Moment M AB = 0 ( L − x)
L
− M0
Shear VAB =
L
− M0 M
Reactions RA = RB = 0
L L

## Simple beam - Couple moment Mo at center

− M0x 2
Deflection y AC = (L − 4x 2 )
24 LEI
M ( L − x) 2
yCB = 0 ( L − 4( L − x) 2 )
24 LEI
− M0 2
Slope θ AC = ( L − 12 x 2 )
24 LEI
M0
θ CB = (12( L − x) 2 − L2 )
24 LEI
− M0 2 M0
θA = ( L − 3b 2 ) θ B = (− L2 + 3a 2 )
6 LEI 6 LEI
M x − M0
Moment M AC = 0 M CB = ( L − x)
L L
M M
Shear VAC = 0 VCB = 0
L L
M0 − M0
Reactions RA = RB =
L L
Simple beam - Couple moment Mo at any point
− M0x 2
Deflection y AC = ( L − 3b 2 − x 2 )
6 LEI
M 0 ( L − x) 2
yCB = ( L − 3a 2 − ( L − x) 2 )
6 LEI
− M0 2
Slope θ AC = ( L − 3b 2 − 3 x 2 )
6 LEI
M0
θ CB = (− L2 + 3a 2 + 3( L − x) 2 )
6 LEI
− M0 2 M0
θA = ( L − 3b 2 ) θB = (− L2 + 3a 2 )
6 LEI 6 LEI
M0x − M0
Moment M AC = M CB = ( L − x)
L L
M M
Shear VAC = 0 VCB = 0
L L
M − M0
Reactions RA = 0 RB =
L L

## Simple beam - Couple moments M1 and M2 at each end (I)

− x( L − x)
Deflection y AB = [( M 1 − M 2 ) x − (2M 1 + M 2 ) L]
6 LEI
Slope:
θ AB =
1
6 LEI
[
( M 1 − M 2 )(3x 2 − 2 Lx) − (2 M 1 + M 2 )(2 Lx − L2 ) ]
1
Moment M AB = [( M 1 − M 2 ) x − LM 1 ]
L
M − M2
Shear VAB = 1
L
M − M2 M − M1
Reactions RA = 1 RB = 2
L L

## Simple beam - Couple moments M1 and M2 at each end (II)

− x( L − x)
Deflection y AB = [( M 1 + M 2 ) x − (2M 1 − M 2 ) L]
6 LEI
Slope:
θ AB =
1
6 LEI
[
( M 1 + M 2 )(3x 2 − 2 Lx) − (2 M 1 − M 2 )(2 Lx − L2 ) ]
1
Moment M AB = [( M 1 + M 2 ) x − LM 1 ]
L
M + M2
Shear VAB = 1
L
M + M2 − M1 − M 2
Reactions RA = 1 RB =
L L
Simple beam - Two equal couple moments Mo at each end
− M0x
Deflection y AB = ( L − x)
2 EI
− M 0 L2 L
y MAX = at x =
8EI 2
− M0 − M0L
Slope θ AB = ( L − 2 x) θ A = −θ B =
2 EI 2 EI
Moment M AB = M 0
Shear VAB = 0
Reactions RA = RB = 0

## Cantilever beam - Uniformly distributed load

− w0 4
Deflection y AB = ( x − 4 Lx 3 + 6 L2 x 2 )
24 EI
− w0 L4
y MAX = y B = at x = L
8EI
− w0 3 − w0 L3
Slope θ AB = ( x − 3Lx 2 + 3L2 x) θ B =
6 EI 6 EI
− w0 − w0 L2
Moment M AB = ( L − x) 2
M MAX = M A =
2 2
Shear VAB = w0 ( L − x)
Reactions RA = w0 L

## Cantilever beam - Uniform load partially distributed at fixed end

− w0
Deflection y AC = (6a 2 x 2 − 4ax 3 + x 4 )
24 EI
− w0 a 3
yCB = (4 x − a )
24 EI
− w0 a 3
y MAX = y B = (4 L − a)
24 EI
− w0
Slope θ AC = (3a 2 x − 3ax 2 + x 3 )
6 EI
− w0 a 3
θ CB = θ C = θ B =
6 EI
− w0
Moment M AC = (a − x) 2 M CB = M C = M B = 0
2
− w0 a 2
M MAX = M A =
2
Shear VAC = w0 (a − x) VCB = VC = VB = 0
Reactions RA = w0 a
Cantilever beam - Uniform load partially distributed at free end

− w0 bx 2
Deflection y AC = (3L + 3a − 2 x)
12 EI
− w0 4
yCB = ( x − 4 Lx 3 + 6 L2 x 2 − 4a 3 x + a 4 )
24 EI
− w0bx
Slope θ AC = ( L + a − x)
2 EI
− w0 3
θ CB = ( x − 3Lx 2 + 3L2 x − a 3 )
6 EI
− w0 3
θB = (L − a3 )
6 EI
− w0 b − w0
Moment M AC = ( L + a − 2 x) M CB = ( L − x) 2
2 2
Shear VAC = VA = VC = w0b VCB = w0 ( L − x)
Reactions RA = w0b

## Cantilever beam - Uniform load partially distributed

− w0bx 2
Deflection y AC = (6a + 3b − 2 x)
12 EI
− w0 4
yCD = ( x − 4(a + b) x 3 + 6(a + b) 2 x 2 − 4a 3 x + a 4 )
24 EI
− w0
y DB = (4 x[(a + b) 3 − a 3 ] − (a + b) 4 + a 4 )
24 EI
− w0 bx
Slope θ AC = ( 2a + b − x )
2 EI
− w0 3
θ CD = ( x − 3(a + b) x 2 + 3(a + b) 2 x − a 3 )
6 EI
− w0
θ DB = ((a + b) 3 − a 3 )
6 EI
− w0 b
Moment M AC = ( 2a + b − 2 x )
2
− w0
M CD = (a + b − x) 2 M DB = M D = M B = 0
2
Shear VAC = VA = VC = w0 b VCD = w0 (a + b − x)
VDB = VD = VB = 0
Reactions RA = w0b
Cantilever beam - Load increasing uniformly to free end

− w0 x 2
Deflection y AB = (20 L3 − 10 L2 x + x 3 )
120 LEI
− 11w0 L4
y MAX = at x = L
120 EI
− w0 x
Slope θ AB = (8L3 − 6 L2 x + x 3 )
24 LEI
− w0 L3
θB =
8EI
− w0
Moment M AB = (2 L3 − 3L2 x + x 3 )
6L
w
Shear VAB = 0 ( L2 − x 2 )
2L
w0 L
Reactions RA =
2

## Cantilever beam - Load increasing uniformly to fixed end

− w0 x 2
Deflection y AB = (10 L3 − 10 L2 x + 5 Lx 2 − x 3 )
120 LEI
w0 L4
yMAX = at x=L
30 EI
− w0 x
Slope θ AB = (4 L3 − 6 L2 x + 4 Lx 2 − x 3 )
24 LEI
− w0 L3
θB =
24 EI
− w0
Moment M AB = ( L − x) 3
6L
w0
Shear VAB = ( L − x) 2
2L
wL
Reactions RA = 0
2
Cantilever beam - Cosinusoidal distributed load
− w0 L ⎛ πx ⎞
Deflection yAB = 4
3
⎜ 48L cos − 48L3 + 3π 3 Lx 2 − π 3 x 3 ⎟
3π EI ⎝ 2L ⎠
− 2w0 L 3 4
y MAX = ( π − 24) at x = L
3π 4 EI
−w L⎛ πx ⎞
Slope θ AB = 3 0 ⎜ 2π 2 Lx − π 2 x 2 − 8L2sin ⎟
π EI ⎝ 2L ⎠
−w L 3
θ B = 3 0 ( π 2 − 8)
π EI
− 2w0 L ⎛ πx ⎞
Moment M AB = 2 ⎜ πL − πx − 2 L cos ⎟
π ⎝ 2L ⎠
2w L ⎛ πx ⎞
Shear VAB = 0 ⎜1 − sin ⎟
π ⎝ 2L ⎠
2 w0 L
Reactions RA =
π

## Cantilever beam - Concentrated load P at free end

−P
Deflection y AB = (3Lx 2 − x 3 )
6 EI
− PL3
y MAX = y B =
3EI
−P
Slope θ AB = (2 Lx − x 2 )
2 EI
− PL2
θ MAX = θ B =
2 EI
Moment M AB = − P ( L − x) M MAX = M A = − PL
Shear VAB = VA = VB = P
Reactions RA = P

## Cantilever beam - Concentrated load P at any point

−P − Pa 2
Deflection y AC = (3ax 2 − x 3 ) yCB = (3x − a)
6 EI 6 EI
− Pa 2
y MAX = y B = (3L − a)
6 EI
−P − Pa 2
Slope θ AC = (2ax − x 2 ) θ CB = θ C = θ B =
2 EI 2 EI
Moment M AC = − P(a − x) M CB = M C = M B = 0
M MAX = M A = − Pa
Shear VAC = VA = VC = P VCB = VC = VB = 0
Reactions RA = P
Cantilever beam - Couple moment Mo at free end

− M 0 x2
Deflection y AB =
2 EI
− M 0 L2
y MAX = at x = L
2 EI
− M0x
Slope θ AB =
EI
Moment M AB = M A = M B = − M 0
Shear VAB = VA = VB = 0
Reactions RA = 0

## Cantilever beam - Couple moment Mo at any point

− M 0 x2 − M 0a
Deflection y AC = yCB = (2 x − a)
2 EI 2 EI
− M 0a
y MAX = (2 L − a) at x = L
2 EI
− M0x − M 0a
Slope θ AC = θ CB = θ C = θ B =
EI EI
Moment M AC = M A = − M 0 M CB = M B = 0
Shear VAC = VA = VC = 0 VCB = VC = VB = 0
Reactions RA = 0

## Fixed-fixed beam - Uniformly distributed load

− w0 x 2
Deflection y AB = ( L − x) 2
24 EI
− w0 x 2
Slope θ AB = ( L − 3Lx + 2 x 2 )
12 EI
− w0 2
Moment M AB = ( L − 6 Lx + 6 x 2 )
12
w0
Shear VAB = ( L − 2 x)
2
wL
Reactions RA = RB = 0
2
Fixed-fixed beam - Uniform load partially distributed at left end (I)

− x2
Deflection y AC = ( w0 x 2 − 4 RA x − 12 M A )
24 EI
3( M B + LRB ) x 2 − RB x 3
yCB = +
6 EI
L2 (3M B + LRB ) − 3(2M B + LRB ) Lx
+
6 EI
−x
Slope θ AC = ( w0 x 2 − 3RA x − 6M A )
6 EI
θ CB =
−1
2 EI
[
RB x 2 − 2( M B + LRB ) x + L(2 M B + LRB ) ]
w x2
Moment M AC = RA x + M A − 0 M CB = RB ( L − x) + M B
2
Shear VAC = RA − w0 x VCB = − RB
3w L M − M B w L M − MB
Reactions RA = 0 − A RB = 0 + A
8 L 8 L
− 11w0 L 2
− 5w0 L 2
Where M A = MB =
192 192

## Fixed-fixed beam - Uniform load partially distributed at left end (II)

− x2
Deflection y AC = ( w0 x 2 − 4 RA x − 12 M A )
24 EI
3( M B + LRB ) x 2 − RB x 3
yCB = +
6 EI
L2 (3M B + LRB ) − 3(2M B + LRB ) Lx
+
6 EI
−x
Slope θ AC = ( w0 x 2 − 3RA x − 6M A )
6 EI
θ CB =
−1
2 EI
[
RB x 2 − 2( M B + LRB ) x + L(2 M B + LRB ) ]
w x2
Moment M AC = RA x + M A − 0 M CB = RB ( L − x) + M B
2
Shear VAC = RA − w0 x VCB = − RB
w ( L + b) a M A − M B
Reactions RA = 0 −
2L L
wa 2
M − MB
RB = 0 + A
2L L
− w0 a 2
Where M A = 2
(6 L2 − 8La + 3a 2 )
12 L
− w0 a 3
MB = (4 L − 3a)
12 L2
Fixed-fixed beam - Uniform load partially distributed

x2
Deflection y AC = (3M A + RA x)
6 EI
yCD =
−1
24 EI
[
w0 ( x − a) 4 − 4 RA x 3 − 12M A x 2]
3( M B + LRB ) x 2 − RB x 3
y DB = +
6 EI
L2 (3M B + LRB ) − 3(2M B + LRB ) Lx
+
6 EI
x
Slope θ AC = (2 M A + RA x)
2 EI
θ CD =
−1
6 EI
[
w0 ( x − a) 3 − 3RA x 2 − 6M A x ]
θ DB =
−1
2 EI
[
RB x 2 − 2( M B + LRB ) x + L(2M B + LRB ) ]
w0 ( x − a) 2
Moment M AC = M A + RA x M CD = RA x + M A −
2
M DB = M B + RB ( L − x)
Shear VAC = RA VCD = RA − w0 ( x − a) VDB = − RB
w (2c + b)b − 2M A + 2M B
Reactions RA = 0
2L
w (2a + b)b + 2M A − 2M B
RB = 0
2L
Where M A =
− w0 b 2
24 L 2
[
b (2 L − 6c − 3b) + (6a + 3b)(2c + b) 2 ]
MB =
− w0b 2
24 L 2
[
b (2 L − 6a − 3b) + (6c + 3b)(2a + b) 2 ]
Fixed-fixed beam - Concentrated load at center

− Px 2
Deflection y AC = (3L − 4 x)
48 EI
− P ( L − x) 2
yCB = (4 x − L)
48EI
− Px −P 2
Slope θ AC = ( L − 2 x) θ CB = ( L − 3Lx + 2 x 2 )
8EI 8EI
−P P
Moment M AC = ( L − 4 x) M CB = (3L − 4 x)
8 8
P −P
Shear VAC = VCB =
2 2
P
Reactions RA = RB =
2
Fixed-fixed beam - Concentrated load at any point

− Pb 2 x 2
Deflection y AC = (3aL − 3ax − bx)
6 EIL3
− Pa 2 ( L − x) 2
yCB = (3bx − aL + ax)
6 EIL3
− Pb 2 x
Slope θ AC = (2aL − 3ax − bx)
2 EIL3
θ CB =
Pa 2 ( L − x)
2 EIL 3
[
x(3b + a) − L2 ]
− Pb 2 x
Moment M AC = (aL − 3ax − bx)
L3
Pa 2
M CB = 3 ( L2 + bL − Lx − 2bx)
L
Pb 2 − Pa 2
Shear VAC = 3 ( L + 2a) VCB = ( L + 2b)
L L3
Pb 2 Pa 2
Reactions RA = 3 ( L + 2a) RB = 3 ( L + 2b)
L L

## Fixed-fixed beam - Two equal concentrated loads symmetrically placed

− Px 2
Deflection y AC = (3aL − 3a 2 − Lx)
6 EIL
− Pa 2
yCD = (3Lx − 3x 2 − aL)
6 EIL
− P ( L − x) 2
y DB = (3aL − 3a 2 − L( L − x))
6 EIL
− Px − Pa 2
Slope θ AC = (2aL − 2a 2 − Lx ) θ CD = ( L − 2 x)
2 EIL 2 EIL
θ DB =
P( L − x)
2 EIL
[2aL − 2a 2 − L( L − x) ]
P
Moment M AC = ( Lx − aL + a 2 )
L
Pa 2 P
M CD = M DB = ( L2 − Lx − La + a 2 )
L L
Shear VAC = P VCD = 0 VDB = − P
Reactions RA = RB = P
Fixed-fixed beam - Couple moment Mo at center

M 0 x2
Deflection y AC = (2 x − L)
8LEI
− M0
yCB = (5 Lx 2 − 2 x 3 − 4 L2 x + L3 )
8LEI
M0x − M0
Slope θ AC = (3x − L) θ CB = (10 Lx − 6 x 2 − 4 L2 )
4 LEI 8LEI
M0 − M0
Moment M AC = (6 x − L) M CB = (5 L − 6 x)
4L 4L
3M 0
Shear VAB =
2L
3M 0 − 3M 0
Reactions RA = RB =
2L 2L

## Fixed-fixed beam - Couple moment Mo at any point

Deflection:
− M 0bx 2 M 0 a( L − x) 2
yAC = (2aL − 2ax − bL) yCB = (2bx − aL)
2 L3 EI 2 L3 EI
Slope:
− M bx M a ( L − x) 2
θ AC = 3 0 (2aL − 3ax − bL) θ CB = 0 3 ( L − 3bx)
L EI L EI
Moment:
− M 0b M a
M AC = 3
(2aL − 6ax − bL) M CB = 03 (6bx − 4bL − aL)
L L
6M 0 ab
Shear VAB =
L3
6M 0 ab − 6M 0 ab
Reactions RA = 3
RB =
L L3
− M 0b M a
Where M A = 2
( 2 a − b) M B = 02 (2b − a)
L L

## Fixed-pinned beam - Uniformly distributed load

− w0 x 2
Deflection y AB = (3L2 − 5Lx + 2 x 2 )
48EI
− w0 x
Slope θ AB = (6 L2 − 15Lx + 8 x 2 )
48EI
− w0 2
Moment M AB = ( L − 5Lx + 4 x 2 )
8
w
Shear VAB = 0 (5L − 8 x)
8
5w0 L 3w L
Reactions RA = RB = 0
8 8
Fixed-pinned beam - Uniform load partially distributed at fixed end
Deflection:
8R L( L − x) 3 − 2w0 L(a − x) 4 − w0 a 3 ( L − x)( L + 3b)
y AC = B
48EIL
8R L( L − x) − w0 a ( L − x)( L + 3b)
3 3
yCB = B
48EIL
Slope:
− 24 RB L( L − x) 2 + 8w0 L(a − x) 3 + w0 a 3 ( L + 3b)
θ AC =
48EIL
− 24 RB L( L − x) + w0 a 3 ( L + 3b)
2
θ CB =
48EIL
2 R ( L − x) − w0 (a − x) 2
Moment M AC = B M CB = RB ( L − x)
2
Shear VAC = − RB + w0 (a − x) VCB = − RB
w ( L + b)a − 2 M A w0 a 2 + 2M A
Reactions RA = 0 RB =
2L 2L
− w0 ( L + b) 2 a 2
Where M A =
8L2

## Fixed-pinned beam - Uniform load partially distributed at supported end

x2
Deflection y AC = ( RA x + 3M A )
6 EI
4 RB L( L − x) 3 − w0 L( L − x) 4
yCB = +
24 EIL
− w0b 2 ( L − x)(bL + 3ab + 6a 2 )
+
48EIL
x
Slope θ AC = ( RA x + 2M A )
2 EI
− 3RB L( L − x) 2 + w0 L( L − x) 3 w0 b 2 (bL + 3ab + 6a 2 )
θ CB = +
6 EIL 48EIL
2 RB ( L − x) − w0 ( L − x) 2
Moment M AC = RA x + M A M CB =
2
Shear VAC = RA VCB = − RB + w0 ( L − x)
w0 b 2 − 2M A w (2a + b)b + 2M A
Reactions RA = RB = 0
2L 2L
− w0b
[ ]
2
Where M A = 2
(2 L + b)( L + a) − b 2
16 L
Fixed-pinned beam - Uniform load partially distributed

x2
Deflection y AC = ( RA x + 3M A )
6 EI
4 R ( L − x) 3 − w0 ( L − x − c) 4
yCD = B +
24 EI

+
[
− w0 b( L − x) 2b 2 L − 3b 2 (2a + b) + 3(2c + b)(2a + b) 2 ]
96 EIL
R ( L − x) 3
y DB = B +
6 EI

+
[
− w0 b( L − x) 2b 2 L − 3b 2 (2a + b) + 3(2c + b)(2a + b) 2 ]
96 EIL
x
Slope θ AC = ( RA x + 2M A )
2 EI
− 3RB ( L − x) 2 + w0 ( L − x − c) 3
θ CD = +
6 EI

+ 0
[
w b 2b 2 L − 3b 2 (2a + b) + 3(2c + b)(2a + b) 2 ]
96 EIL
− RB ( L − x) 2
θ DB = +
2 EI

+
[
w0b 2b 2 L − 3b 2 (2a + b) + 3(2c + b)(2a + b) 2 ]
96 EIL
Moment M AC = RA x + M A
2 RB ( L − x) − w0 ( L − x − c) 2
M CD = M DB = RB ( L − x)
2
Shear VAC = RA VCD = w0 ( L − x − c) − RB VDB = − RB
w b(2c + b) − 2M A
Reactions RA = 0
2L
w0 (2a + b)b + 2M A
RB =
2L

Where M A =
[
− w0 (2c + b)(2a + b)b (2 L + 2c + b)(2a + b) − b 2 ]
16 L2
Fixed-pinned beam - Concentrated load at center
Deflection:
− Px 2 − P( L − x)
y AC = (9 L − 11x) yCB = (3L2 − 5( L − x) 2 )
96 EI 96 EI
Slope:
− Px −P
θ AC = (6 L − 11x) θ CB = (4 L2 − 10 Lx + 5 x 2 )
32 EI 32 EI
−P 5P
Moment M AC = (3L − 11x) M CB = ( L − x)
16 16
11P − 5P
Shear VAC = VCB =
16 16
11P 5P
Reactions RA = RB =
16 16

## Fixed-pinned beam - Concentrated load at any point

− Pbx 2
Deflection y AC = 3
(3L3 − 3b 2 L − 3L2 x + b 2 x)
12 EIL
− Pa 2 ( L − x)
yCB = (3bL2 − (2 L + b)( L − x) 2 )
12 EIL3
− Pbx
Slope θ AC = 3
(2 L3 − 2b 2 L − 3L2 x + b 2 x)
4 EIL
− Pa 2
θ CB = (2 L3 − 4 L2 x − 2bLx + 2 Lx 2 + bx 2 )
4 EIL3
Moment:
− Pb 3 Pa 2
M AC = ( L − b 2
L − 3 L2
x + b 2
x ) M CB = ( L − x)(2 L + b)
2 L3 2 L3
Pb − Pa 2
Shear VAC = 3 (3L2 − b 2 ) VCB = ( 2 L + b)
2L 2 L3
Pb Pa 2
Reactions RA = 3 (3L2 − b 2 ) RB = 3 (2 L + b)
2L 2L
Fixed-pinned beam - Two equal concentrated loads symmetrically placed
Deflection:
y AC =
Px 2
12 EIL 2
[
(3a 2 − 3aL − 2 L2 )( L − x) + 2 L(3a 2 − 3aL + L2 ) ]
− Pa(3( L − a)( L − x) 3 − 6 L2 ( L − x) 2 )
yCD = +
12 EIL2

+
[ ]
− Pa 3L2 ( L + a )( L − x) − 2 L2 a 2
12 EIL2
y DB =
− P( L − x)
12 EIL 2
[
(3aL − 3a 2 − 2 L2 )( L − x) 2 + 3aL2 ( L − a) ]
Slope:
θ AC =
Px
12 EIL 2
[
(3a 2 − 3aL − 2 L2 )(2 L − 3x) + 4 L(3a 2 − 3aL + L2 ) ]
θ CD =
− Pa
4 EIL 2
[ ]
− 3( L − a)( L − x) 2 + 4 L2 ( L − x) − L2 ( L + a )

θ DB =
P
4 EIL2
[ ]
(3aL − 3a 2 − 2 L2 )( L − x) 2 + aL2 ( L − a)
P
[
Moment M AC = 2 3a 2 L − 3aL2 + x(2 L2 + 3aL − 3a 2 )
2L
]
M CD =
− Pa
2L 2
[ ]
3( L − a)( L − x) − 2 L2
− P( L − x)
M DB = 2
(3aL − 3a 2 − 2 L2 )
2L
P 3Pa( L − a)
Shear VAC = 2 (2 L2 + 3aL − 3a 2 ) VCD =
2L 2 L2
P
VDB = 2 (3aL − 3a 2 − 2 L2 )
2L
P
Reactions RA = 2 (2 L2 + 3aL − 3a 2 )
2L
P
RB = 2 (3a 2 + 2 L2 − 3aL)
2L
Fixed-pinned beam - Couple moment Mo at any point

Deflection: y AC =
− M 0 x2
4 EIL 3
[
2b 2 L − ( L − x)( L2 − b 2 )]
yCB =
− M 0 a( L − x)
4 EIL 3
[ − 4 L3 − (( L − x) 2 − 3L2 )( L + b) ]
Slope θ AC =
− M0x
4 EIL 3
[
4b 2 L − (2 L − 3x)( L2 − b 2 ) ]
θ CB =
− M 0a 3
4 EIL3
[
4 L − 3( L + b)( x 2 − 2 Lx) ]
Moment M AC =
− M0
2L 3
[
2b 2 L − ( L − 3x)( L2 − b 2 )]
3M 0 a
M CB = ( L + b)( L − x)
2 L3
− 3M 0 a
Shear VAB = ( L + b)
2 L3
− 3M 0 a 3M 0 a
Reactions RA = 3
( L + b) RB = ( L + b)
2L 2 L3

## Fixed-pinned beam - Couple moment Mo at supported end

M 0 x 2 ( L − x)
Deflection y AB =
4 EIL
M x(2 L − 3 x)
Slope θ AB = 0
4 EIL
M ( L − 3 x)
Moment M AB = 0
2L
− 3M 0
Shear VAB =
2L
− 3M 0 3M 0
Reactions RA = RB =
2L 2L
Overhanging beam - Uniformly distributed load
− w0 x 4
Deflection y AB = ( L − 2 L2 x 2 + Lx 3 − 2a 2 L2 + 2a 2 x 2 )
24 LEI
− w0 x1 2 3
y BC = (4a 2 L − L3 + 6a 2 x1 − 4ax1 + x1 )
24 EI
− w0
Slope θ AB = ( L4 − 6 L2 x 2 + 4 Lx 3 − 2a 2 L2 + 6a 2 x 2 )
24 LEI
− w0
θ BC = 2
(4a 2 L − L3 + 12a 2 x1 − 12ax1 + 4 x1 )
3

24 EI
wx − w0
Moment M AB = 0 ( L2 − Lx − a 2 ) M BC = (a − x1 ) 2
2L 2
w0 2
Shear VAB = ( L − 2 Lx − a 2 ) VBC = w0 (a − x1 )
2L
w w
Reactions RA = 0 ( L2 − a 2 ) RB = 0 ( L + a) 2
2L 2L
Where x1 = x − L

## Overhanging beam - Uniformly distributed load on overhang

w0 a 2 x 2
Deflection y AB = (L − x 2 )
12 LEI
− w0 x1 2 3
y BC = (4a 2 L + 6a 2 x1 − 4ax1 + x1 )
24 EI
w a2
Slope θ AB = 0 ( L2 − 3x 2 )
12 LEI
− w0 2
θ BC = 2
(a L + 3a 2 x1 − 3ax1 + x1 )
3

6 EI
− w0 a 2 x − w0
Moment M AB = M BC = (a − x1 ) 2
2L 2
− w0 a 2
Shear VAB = VBC = w0 (a − x1 )
2L
− w0 a 2 w (2 L + a )a
Reactions RA = RB = 0
2L 2L
Where x1 = x − L
Overhanging beam - Concentrated load at end of overhang
Pax 2
Deflection y AB = (L − x 2 )
6 LEI
− Px1 2
y BC = (2aL + 3ax1 − x1 )
6 EI
Pa −P
Slope θ AB = ( L2 − 3x 2 ) θ BC =
2
(2aL + 6ax1 − 3 x1 )
6 LEI 6 EI
− Pax
Moment M AB = M BC = − P(a − x1 )
L
− Pa
Shear VAB = VBC = P
L
− Pa P( L + a)
Reactions RA = RB =
L L
Where x1 = x − L

## Overhanging beam - Concentrated load at any point between supports

− Pbx 2
Deflection y AC = (L − b2 − x2 )
6 LEI
− Pa( L − x)
yCB = (2 Lx − a 2 − x 2 )
6 LEI
Pabx1
y BD = ( L + a)
6 LEI
− Pb 2
Slope θ AC = ( L − b 2 − 3x 2 )
6 LEI
− Pa Pab( L + a)
θ CB = (2 L2 − 6 Lx + a 2 + 3 x 2 ) θ BD =
6 LEI 6 LEI
Pbx Pa
Moment M AC = M CB = ( L − x) M BD = 0
L L
Pb − Pa
Shear VAC = VCB = VBD = 0
L L
Pb Pa
Reactions RA = RB =
L L
Where x1 = x − L

## Try BEAM DEFLECTION CALCULATOR at vaxasoftware.com

www.vaxasoftware.com